Post-Vaccination Coronavirus Disease 2019: A Case-Control Study and Genomic Analysis of 119 Breakthrough Infections in Partially Vaccinated Individuals . (19th August 2021) - Baltas, Ioannis; Boshier, Florencia A T; Williams, Charlotte A; Bayzid, Nadua; Cotic, Marius; Afonso Guerra-Assunção, José; Irish-Tavares, Dianne; Haque, Tanzina; Hart, Jennifer; Roy, Sunando; Williams, Rachel; Breuer, Judith; et al.
Abstract: Background: Post-vaccination infections challenge the control of the coronavirus disease 2019 (COVID-19) pandemic. Methods: We matched 119 cases of post-vaccination severe acute respiratory syndrome coronavirus 2 infection with BNT162b2 mRNA or ChAdOx1 nCOV-19 to 476 unvaccinated patients with COVID-19 (September 2020–March 2021) according to age and sex. Differences in 60-day all-cause mortality, hospital admission, and hospital length of stay were evaluated. Phylogenetic, single-nucleotide polymorphism (SNP), and minority variant allele (MVA) full-genome sequencing analysis was performed. Results: Overall, 116 of 119 cases developed COVID-19 post–first vaccination dose (median, 14 days). Thirteen of 119 (10.9%) cases and 158 of 476 (33.2%) controls died ( P  < .001), corresponding to the 4.5 number needed to treat (NNT). Multivariably, vaccination was associated with a 69.3% (95% confidence interval [CI]: 45.8 to 82.6) relative risk (RR) reduction in mortality. Similar results were seen in subgroup analysis for patients with infection onset ≥14 days after first vaccination and across vaccine subgroups. Hospital admissions (odds ratio, 0.80; 95% CI: .51 to 1.28) and length of stay (–1.89 days; 95% CI: –4.57 to 0.78) were lower for cases, while cycle threshold values were higher (30.8 vs 28.8, P  = .053). B.1.1.7 was the predominant lineage in cases (100 of 108, 92.6%) and controls (341 of 446, 76.5%). Genomic analysis identified 1 post-vaccination case that harbored the E484K vaccine-escape mutation (B.1.525 lineage). Conclusions: Previous vaccination reduces mortality when B.1.1.7 is the predominant lineage. No significant lineage-specific genomic changes during phylogenetic, SNP, and MVA analysis were detected. Abstract : Previous vaccination with either BNT162b2 or ChAdOx1 reduces 60-day mortality from coronavirus disease 2019 from the B0.1.1.7 lineage by 69.3%. Breakthrough infections are not primarily driven by viral genomic mutations.